Manajemen Risiko: Pendekatan BPRIM pada Proses Bisnis Administrasi Kependudukan - Ainus Sukma El Diana Putri; Indri Sudanawati Rozas; Mohammad Khusnu Milad (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Risk management within an organization is important. The risk cannot be left alone, because in the end it will get bigger and have a bad impact on the organization. Risk management is an attempt to identify vulnerabilities and threats to information sources used by an organization. This study aims to see the results of the implementation of risk management in the electronic-based population administration business process, named POEDAK (Population Administration Online Services), in Gresik district. In this study, a risk analysis was carried out using the risk register and risk analysis using BPRIM. This risk analysis is carried out to determine the category of each existing risk, as well as to see the results of the analysis from the risk register and BPRIM. From the risk analysis that has been carried out using the risk register and BPRIM, the results obtained from the risk register and the depiction of the risk diagram using BPRIM are stated that with reference to BPMN POEDAK there are 16 risk codes. From the 16 risk codes, there are 12 risks in the low level category and 4 risks in the important level category. Where the risk is in the low category, namely the risk with the risk code R4, R5, R6, R7, R8, R9, R10, R11, R12, R14, R15, and R16. Meanwhile, the risks that fall into the important category are risks with codes R1, R2, R3, and R13.